The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.neuropsychologia.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory span in autopsy-confirmed Dementia with Lewy Bodies and Alzheimer's Disease

Abstract: Evidence from patients with amnesia suggests that recognition memory span tasks engage both long-term memory (i.e., secondary memory) processes mediated by the diencephalic-medial temporal lobe memory system and working memory processes mediated by fronto-striatal systems. Thus, the recognition memory span task may be particularly effective for detecting memory deficits in disorders that disrupt both memory systems. The presence of unique pathology in fronto-striatal circuits in Dementia with Lewy Bodies (DLB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…These findings are in line with previous reports made on cohorts with a pathological confirmation of diagnoses. Indeed, numerous studies suggested that severe amnesia could be observed in patients with non-AD or mixed AD pathology, such as DLB (Kraybill et al, 2005;Yoshizawa et al, 2013;Salmon et al, 2015), FTLD (Elgren et al, 1993;Grahan et al, 2005;, or to a lesser degree VaD (Jicha et al, 2006;Reed et al, 2007). This last decade, memory impairment was reported in clinicallydefined DLB (Petrova et al, 2015;Molano et al, 2010), in the clinical subtypes of FTLD such as behavioural variant frontotemporal dementia (Hornberger et al, 2010;Bertoux et al, 2014), semantic progressive aphasia (Casaletto et al, 2017), non-fluent progressive aphasia (Ramanan et al, 2016), amyotrophic lateral sclerosis (Mantovan et al, 2003), progressive supranuclear palsy (Kobylecki et al, 2015) as well as in clinically-defined VaD (Mathias & Burke, 2009) although inconsistent findings were reported in this disease due to the variable topography of vascular lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in line with previous reports made on cohorts with a pathological confirmation of diagnoses. Indeed, numerous studies suggested that severe amnesia could be observed in patients with non-AD or mixed AD pathology, such as DLB (Kraybill et al, 2005;Yoshizawa et al, 2013;Salmon et al, 2015), FTLD (Elgren et al, 1993;Grahan et al, 2005;, or to a lesser degree VaD (Jicha et al, 2006;Reed et al, 2007). This last decade, memory impairment was reported in clinicallydefined DLB (Petrova et al, 2015;Molano et al, 2010), in the clinical subtypes of FTLD such as behavioural variant frontotemporal dementia (Hornberger et al, 2010;Bertoux et al, 2014), semantic progressive aphasia (Casaletto et al, 2017), non-fluent progressive aphasia (Ramanan et al, 2016), amyotrophic lateral sclerosis (Mantovan et al, 2003), progressive supranuclear palsy (Kobylecki et al, 2015) as well as in clinically-defined VaD (Mathias & Burke, 2009) although inconsistent findings were reported in this disease due to the variable topography of vascular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the excessive confidence in the specificity of amnesia may also have negatively impacted the differential dementia diagnosis , as the presence of severe amnesia in frontotemporal lobar degeneration (FTLD), dementia with Lewy bodies (DLB), vascular dementia (VaD) (Elfrgen et al, 1993;Kraybill et al, 2005;Graham et al, 2005;Jicha et al, 2006;Reed et al, 2007;Mathias & Burke, 2009;Hornberger et al, 2010;Yoshizawa et al, 2013;Bertoux et al, 2014;Petrova et al, 2015;Salmon et al, 2015) and psychiatric cases has been since reported (Kizilbash et al, 2002;Lee et al, 2012). Moreover, most of the studies assessing amnesia in AD lacked pathological confirmation (Pasquier et al, 2001;Sarazin et al, 2007;Teichmann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical value of the SRT is demonstrated by studies using the SRT to assess verbal memory function in patients with either acquired head injury (Leitner, Miller, & Libben, 2017), multiple sclerosis (Krupp, & Elkins, 2000), epilepsy (Bell et al, 2005), neurodegenerative and psychiatric disorders (including depression, schizophrenia and post-traumatic stress disorder) (Campo, Morales, & MartĂ­nez-Castillo, 2003; Goldberg et al, 1989; Semkovska, & McLoughlin, 2010; Vermetten et al, 2003). It is further supported by its ability to differentiate between different types of neurodegenerative disorders (Salmon et al, 2015) and its ability to predict progression from age-associated cognition to mild cognitive impairment (Blacker et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among numerous cognitive domains, working memory serves as the basis of other higher order cognitive processes including but not limited to recognition memory ( 27 – 29 ), which is mediated by mPFC function. In order to compare the effects of d-amphetamine and lisdexamfetamine on mPFC-associating cognition, we focused on the two types of memory: spatial working memory and spatial recognition memory using Y-maze-based spontaneous alternation task ( 30 , 31 ) and two-trial delayed alteration ( 32 ) task respectively.…”
Section: Introductionmentioning
confidence: 99%